Macromol. Rapid Commun. 16/2013. Issue 16 (19th August 2013) - Zhang, Jianqi; Posselt, Dorthe; Sepe, Alessandro; Shen, Xuhu; Perlich, Jan; Smilgies, Detlef‐M.; Papadakis, Christine M.
<x xml:space="preserve">Abstract</x> Time‐resolved grazing‐incidence smallangle X‐ray scattering is used to investigate the structural changes in a lamellar block copolymer thin film during solvent vapor treatment and drying. Drastic changes proceed at the film surface: During solvent vapor treatment, the film surface is covered by one of the blocks. During drying, this thin surface layer retracts, and protrusions of the other block are formed. Further details can be found in the article by J. Zhang, D. Posselt, A. Sepe, X. Shen, J. Perlich, D.‐M. Smilgies, and C. M. Papadakis* on page 1289. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>